1998
DOI: 10.1097/00006254-199807000-00006
|View full text |Cite
|
Sign up to set email alerts
|

Fetal Fibronectin, Endotoxin, Bacterial Vaginosis and Cervical Length as Predictors of Preterm Birth and Neonatal Morbidity in Twin Pregnancies

Abstract: Objective To evaluate the predictive values of fetal fibronectin, bacterial vaginosis, endotoxin and cervical length for preterm birth (< 35 and < 37 weeks) and neonatal morbidity in twin pregnancies.Participants One-hundred and twenty-one women with twin pregnancies recruited into a prospective longitudinal study at three antenatal clinics in the southwest of Sweden.Methods Cervical or vaginal fluid was sampled and determined for fetal fibronectin (2 0.05 pg/mL was used as cutoff), endotoxin (2 100 pg/mL) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
33
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(34 citation statements)
references
References 2 publications
1
33
0
Order By: Relevance
“…Ten studies (67%) were performed in the United States [28, 29, 32, 33, 3539, 41], and one each in Italy [27], Sweden [30], Brazil [31], United Kingdom [34], and France [40]. The sample size ranged from 29 [28] to 169 [36] in asymptomatic women and from 38 [38] to 87 [41] in symptomatic women.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ten studies (67%) were performed in the United States [28, 29, 32, 33, 3539, 41], and one each in Italy [27], Sweden [30], Brazil [31], United Kingdom [34], and France [40]. The sample size ranged from 29 [28] to 169 [36] in asymptomatic women and from 38 [38] to 87 [41] in symptomatic women.…”
Section: Resultsmentioning
confidence: 99%
“…The sample size ranged from 29 [28] to 169 [36] in asymptomatic women and from 38 [38] to 87 [41] in symptomatic women. Cervicovaginal fetal fibronectin was measured using enzyme-linked immunoabsorbent assay quantitative method (nine studies [2830, 33, 3539]), membrane immunoassay qualitative method (three studies [27, 31, 34]), and rapid TLi system qualitative method (one study [41]). Two studies [32, 40] did not report method for measuring fetal fibronectin.…”
Section: Resultsmentioning
confidence: 99%
“…A Swedish study with 121 twin pregnancies reported that all patients with a positive fFN screening result between 24 and 34 weeks had a subsequent preterm birth before 35 weeks' gestation and that the predictive value was higher for fFN than cervical length. 32 One potential explanation for this discordance in results is that a positive FFN may be more predictive of a preterm birth as it is associated with both spontaneous preterm labor as well as PPROM, whereas a shortened cervical length has not been associated with preterm premature rupture of membranes in multifetal gestations. 33 A retrospective cohort study with routine fFN and cervical length screening for all twin gestations showed improved rates of antenatal corticosteroid administration within 7 days of delivery when both screening modalities were used to identify women at risk for preterm delivery.…”
Section: Spontaneous Preterm Birth In Multiples 657mentioning
confidence: 99%
“…Eight studies examined the use of fibronectin as a screening tool in low risk pregnancy and nine as a selective screening tool in high risk pregnancy. Most studies 75 Goldenberg (1996) 75 Goldenberg (1996) 75 Goldenberg (1996) 75 Chang (1997) 25 Nageotte (1994) 66 Oliveira (1998) 67 Morrison (1996) 40 Morrison (1996) 40 Goldenberg (2000) 77 Heath (2000) 45 Tolino (1996) 41 Goldenberg (1997) 76 Wennerholm (1997) 94 Goldenberg (1996) Tolino (1996) 41 Wennerholm (1997) 94 Hux (1995) 78 Overall (95% CI) were carried out during the second trimester or early in the third trimester. Meta-regression analysis showed the accuracy of the test did not depend on the method of testing, how often the test was done, classification of risk, or gestation at testing.…”
Section: Fibronectin Test In Asymptomatic Womenmentioning
confidence: 99%
“…Metaregression analysis showed that the accuracy of the test did not depend on the method of testing, how often the test was done, or classification of risk. As for asymptomatic women, the accuracy of the in predicting sponGarcia (1999) 71 Greenhagen (1996) 72 Di Stefano (1999) 27 Zamora (2000) 73 Chang (1997) 25 Roubille (1999) 84 Nageotte (1994) 66 Nageotte (1994) 66 Bittar (1996) 23 Bittar (1996) 23 Nageotte (1994) 66 Oliveira (1998) 67 Nageotte (1994) 66 Leeson (1996) 61 Leeson (1996) 61 Krems (1995) 69 Goldenberg (2000) 77 Lockwood (1993) 80 Tolino (1996) 41 Lockwood (1993) 80 Tolino (1996) 41 Goldenberg (1997) 76 Wennerholm (1997) 94 Goldenberg (1996) 75 Hellemans (1995) 43 Crane (1999) 44 Faron (1997) 42 Hux (1995) 78 Inglis (1994) 79 Crane (1999) 44 Vercoustre (1996) Figure 9 shows the summary receiver operating characteristic curve for symptomatic women. Figures 10, 11, and 12 give details of individual results used to create the summary curve.…”
Section: Fibronectin Test In Symptomatic Womenmentioning
confidence: 99%